METHODS OF EXPRESSING VERBAL POLITENESS BASED ON LIES IN SPANISH FOLK TALES - Tursunova Parvina Mamurjonovna (Western European Studies, 2025)
This article examines how politeness based on lies is expressed in Spanish folk tales. The research analyzes the pragmatic functions of characters' false statements in the process of communication. It has been established that lies in fairy tales are often used to maintain social order, avoid conflicts or punishment, as well as a tool for manipulation. "White lies" (mentira piadosa) are particularly common, serving the function of speech politeness. The speech culture of the Spanish people, as reflected through folklore, demonstrates the linguocultural features of communication.
Keywords: Spanish folk tales; politeness; lies